Network Capability in SMEs: State Of the Art and Future Research Directions - Pujianto, Wahyu Eko; Ranti Putri, Bella May; Ourrota Aini, Nafia Ilhama; Kamila, Edita Rachma (Jurnal Economic Resource, 2025)
The purpose of this study is to systematically review existing research on network capability which remains fragmented. This study aims to fill the gap in the literature by scientifically discussing the contributions and highlighting key issues with previous research findings regarding the dimensions that compose it, as well as the antecedents and consequences of network capability. This study analyzed research related to network capability from 1999-2024 with a total of 67 studies out of 200 in Scopus. The findings also show that existing research has found a number of antecedents and consequences to organizations. On the other hand, this study provides a comprehensive and critical systematization of the limited network capability academic literature. This study also offers opportunities for further research to address the limitations of empirical testing of network capability constructs, antecedents, moderators, mediators, and consequences from various studies.